2010
DOI: 10.1007/s00213-010-1941-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin2A receptor blockade and clinical effect in first-episode schizophrenia patients treated with quetiapine

Abstract: Taken together, the data point to a therapeutic role of the serotonin2A receptor in the treatment of subgroups of patients with schizophrenia. Specifically, the study indicates a serotonin2A receptor associated therapeutic window on positive symptoms in responding patients in the range between 60% and 70% occupancy in antipsychotic-naïve first-episode schizophrenia. We speculate that non-responding patients need higher dopamine D(2) receptor blockade. Future studies with concurrent measurement of interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…**p<0.01, significant decrease in DI compared with the vehicle group. # p<0.05, significant reversal in DI compared with PCP group study which measured 5-HT 2A receptor occupancy with [ 18 F] altanserin PET in 15 first-episode antipsychotic-naïve schizophrenia patients before and after 6 months of quetiapine treatment reported that a 5-HT 2A receptor occupancy level between 60% and 70% appeared to exert the optimal 5-HT 2A receptor-related treatment effect on positive symptoms (Rasmussen et al 2010). It is noteworthy that co-administration of LY379268 and sub-effective doses of the atypical APDs, clozapine and lurasidone, but not haloperidol or pimavanserin, ameliorated the subchronic PCP-induced NOR deficit.…”
Section: Discussionmentioning
confidence: 91%
“…**p<0.01, significant decrease in DI compared with the vehicle group. # p<0.05, significant reversal in DI compared with PCP group study which measured 5-HT 2A receptor occupancy with [ 18 F] altanserin PET in 15 first-episode antipsychotic-naïve schizophrenia patients before and after 6 months of quetiapine treatment reported that a 5-HT 2A receptor occupancy level between 60% and 70% appeared to exert the optimal 5-HT 2A receptor-related treatment effect on positive symptoms (Rasmussen et al 2010). It is noteworthy that co-administration of LY379268 and sub-effective doses of the atypical APDs, clozapine and lurasidone, but not haloperidol or pimavanserin, ameliorated the subchronic PCP-induced NOR deficit.…”
Section: Discussionmentioning
confidence: 91%
“…One PET binding study showed relevant DA D2 receptor occupancy even at low plasma levels in healthy controls (Nord et al, 2011), and 2 other PET studies suggest that possibly both the DA D2 and the 5HT2A receptor occupancy increase with increasing dose of QT (Kapur et al, 2000; Gefvert et al, 2001). However, other treatment studies show both a prominent cortical binding to 5HT2A receptors (Rasmussen et al, 2011) and a predominant striatal binding to dopaminergic receptors (Pavics et al, 2004) even at rather low therapeutic doses. Thus, we cannot be absolutely certain about the pharmacological specificity of the QT effects alone.…”
Section: Discussionmentioning
confidence: 98%
“…With the radiotracer altanserin, a 65% block was observed after 6 month treatment with 300 mg quetiapine [56]. The affinity of altanserin and quetiapine for 5-HT 2 A receptor was described with a K i value of 0.3 nM (Tan et al, 1999) and 264 nM, respectively.…”
Section: Methodsmentioning
confidence: 99%